RELATIONSHIP BETWEEN LIFE STYLE WITH THE DEGREE OF HYPERTENSION AT PUBLIC HEALTH CENTER PEKAUMAN BANJARMASIN - ahmad Syahlani; MOCHDARI MOCHDARI (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2015)
ABSTRACTBackground:Life style is an important factor which greatly affects people's lives. Unhealthy lifestyle, can lead to hypertension, for example; Food, physical activity, stress, and smoking.Methods:The study design used in this research is analytic survey with cross sectional approachwith a sample size of 30 patients who were treated in primary and accidental samplingtechnique. Collecting data using the instruments tool life style questionnaire, and then analyzedusing the Spearman Rank(Rho) with a significant p value0.05.Results:The results showed a good life style that is 16.7% and unhealthy life style that is 83.3%.In the analysis by Rank Spearman correlation test results obtained p =0.0150.05 with r=0.442which means the relationship between life style with the degree of hypertension included in thecategory of medium level of closeness.Conclusion:The presence of Relationship Between Life style With Hypertension Degrees inPublic Health Center Pekauman Banjarmasin.Keywords:life style, degree of hypertension.